FEATURES OF RATIONAL NUTRITION OF STUDENTS IN MODERN EDUCATIONAL INSTITUTIONS - Тимощук, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
One of the most important and most important components of the healthy lifestyle of modern students and students is a healthy diet, which is a prerequisite for the normal functioning of the young growing organism. A high level of work ability, quick and comfortable adaptation to the learning environment, a new team of students and students depends on their state of health, the optimal combination of work and rest, a balanced diet, the presence or absence of bad habits, motor regimes, etc. [1, 2]. Many Ukrainian and foreign scientists (M.P. Gulich, O.M. Grigorenko, A.F. Doronin, A.I. Zharinov, L.V. Kaprilyants, A.G. Klionov, A.) are engaged in the development of modern scientific theories of nutrition. A. Pokrovsky, V.I. Smolyar, A. M. Ugolov, L.F. Shchelkunov, D. S. Jarvis, K. Monastyrsky, A. Robertson, G. Shelton) [3, 4, 6]. With food in the body all the building materials of organs and tissues - proteins, fats, carbohydrates, minerals, salts, vitamins, and water. One of the most important factors in the environment, which greatly affects the processes of life, is a rational nutrition, the main principle of which is its balance and rational mode. Nutrition plays an important role in the course of physiological processes in the body of children and adolescents and resistance to adverse environmental factors.